Integrasi Agama dan Sains melalui Tafsīr ‘Ilmī (Mempertimbangkan Signifikansi dan Kritiknya) - Ach Maimun (Institut Ilmu Keislaman Annuqayah, 2019)
The article aims to evaluate the integration of religion and science in tafsīr ‘ilmī. The attempts to integrate religion and science has been performed in multiple ways, and tafsīr ‘ilmī, which has transformed three times throughout history, is one of the most considerable approaches. The significances are the following: (1) revealing the aspect of i’jāz in al-Quran, (2) strengthening Moslems faith, and (3) making them be more confident. It is inspired by normative, theological, and epistemological arguments of various ulama (scholars), such as al-Ghazali and al-Suyuthi. However, many scholars and scientist criticize tafsīr ‘ilmī’s dimensions, particularly its linguistic (including the lexicology, philology, and literature), theological, and epistemological dimension. In the Islamic scientific discourse, the scientists criticize the methods due to the subject matter is 1) outside the scientific field, 2) unverifiable, 3) and scientifically unproductive. Indeed, Fazlur Rahman and Golshani argue the attempt is contrary to al-Quran’s vision to developing science. Although the critique does not lead tafsīr ‘ilmī to be outright invalid, tafsīr ‘ilmī need to weigh these several considerations: 1) the examination should be compatible with the basic purposes of al-Quran as the book of guidance, 2) the objective is to elucidate al-Quran’s messages and strengthen the faith, 3) the direction is to maximalizes the quality of the people with science, and 4) scientific explanation is an elaboration or illustration (tausī’), and not an interpretation. All things considered, as a model to integrate Islam and science, tafsīr ‘ilmī is artificial and not ideal.